Extractive industries: imperatives, opportunities, and dilemmas in the net-zero transition - Tony Addison; Alan Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
The extractives industries are highly controversial but remain vitally important in much of the developing world. This paper considers their role in reducing energy poverty and discusses scenarios for the future of the global markets for oil, gas, and metals (emphasizing the increasing importance of Asia). It then provides a snapshot of the increasing dependence of many developing countries on the extractives sector and uses that analysis to provide a perspective on the new opportunities arising from the global net-zero transition. Finally, the paper sets out six dilemmas arising from the role of the extractive industries under the sub-headings of: poverty reduction and nature; mining and environmental risk; demand and supply imbalances; fragile states and supply chains; strategic dependence; and technological backwardness. Overall, the paper seeks to sketch the context, both national and global, in which policy-makers must make often hard choices.
Keywords: C81; C82; L72; Q02; 330; climate; commodities; extractive industries; mining; natural gas; oil